Central venous access device Securement and dressing effectiveness: The CASCADE pilot randomised controlled trial in the adult intensive care. Issue 5 (September 2020) - Mitchell, Marion L.; Ullman, Amanda J.; Takashima, Mari; Davis, Chelsea; Mihala, Gabor; Powell, Madeleine; Gibson, Victoria; Zhang, Li; Bauer, Michelle; Geoffrey Playford, E.; Rickard, Claire M.
Abstract: Introduction: Central venous access devices (CVADs) are a vital medical device for intensive care (ICU) patients; however, complications and failure are common, yet potentially prevented through effective dressings and securement. Objectives/aims: The objective of this study was to test the feasibility of a randomised controlled trial (RCT) comparing standard care with three dressing and securement products to prevent CVAD failure. Secondary aims included comparing dressing and securement products on CVAD failure, microbial colonisation, and intervention costs. Methods: A single-centre pilot RCT of ICU adult patients requiring CVADs for >24 h were randomised to four groups: (i) sutures plus chlorhexidine gluconate (CHG) dressing (standard care); (ii) standard care plus tissue adhesive (TA); (iii) two sutureless stabilisation devices (SSD) plus CHG dressing; (iv) sutures, CHG disc plus integrated securement dressing (ISD). Descriptive statistics assessed feasibility. Incidence rates (IRs) of CVAD failure were reported, with group differences compared using the Fisher exact and log-rank tests. Cox regression explored univariable risks for failure. A substudy examined bacterial colonisation of catheter tips, dressings, and skin. Cost estimates of the intervention were compared. Results: A total of 121 participants were randomised. Study feasibility was established with no withdrawal and moderate staff acceptability; however, recruitment was low at 12%. Overall CVAD failure was seen in 14 of 114 (12%) CVADs (19 per 1000 catheter-days); highest in the SSD group (IR: 27.3 per 1000 catheter-days [95% confidence interval CI: 11.4–65.6]), followed by the standard care group (IR: 22.3 per 1000 catheter-days [95% CI: 8.38–59.5]) and TA group (IR: 20.6 per 1000 catheter-days [95% CI: 6.66–64.0]), and lowest in the ISD group (IR: 8.8 per 1000 catheter-days [95% CI: 2.19–35.0]). The majority of complications (11/14, 79%) were suspected central line-associated bloodstream infection (CLABSI), of which only one was laboratory confirmed (standard care group). The cost per patient was lowest in the standard care group by an average difference of AUD $14. Conclusion(s): A large multisite RCT examining forms of securement and dressing is feasible. ISD is the highest priority to test further as it had the lowest failure rate. Trial registration: ACTRN12615000667516 Protocol: https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx? id = 368765